XDR typhoid in Pakistan: A threat to global health security and a wake-up call for antimicrobial stewardship. - Muhammad Ahmed Abdullah; Babar Tasneem Shaikh; Maryam Ashraf; Shahzad Ali Khan (PLoS Neglected Tropical Diseases)
Extensively drug-resistant (XDR) typhoid, caused by Salmonella enterica serotype Typhi, has emerged as a critical global health security threat, with Pakistan, particularly Sindh province, at its epicenter. The misuse of antibiotics, inadequate diagnostic tools, and poor water and sanitation infrastructure have created ideal conditions for the rise of antimicrobial resistance (AMR). XDR typhoid strains resistant to multiple first-line antibiotics have been linked to environmental contamination, with urban areas like Karachi demonstrating high rates of waterborne transmission. International travel has amplified this threat, exporting cases to countries including the United States, the United Kingdom, and Canada, thus highlighting its global implications. This commentary examines the historical context of typhoid treatment, the drivers of AMR in Pakistan, and the critical role of antimicrobial stewardship in combating XDR typhoid. It advocates for an integrated approach that would encompass improvements in water quality, expanded vaccination coverage with typhoid conjugate vaccines (TCVs), and stringent audit of antibiotic prescription practices. Immediate local and global action is needed to contain this public health crisis and prevent the resurgence of typhoid as a largely untreatable disease. This situation underscores the urgency of addressing AMR to safeguard global health security.